OVULE, FRUIT, AND SEED DEVELOPMENT OF ORECTANTHE SCEPTRUM AND ITS SYSTEMATIC RELEVANCE TO XYRIDACEAE (POALES) - Oriani, Aline [UNESP]; Scatena, Vera L. [UNESP] (Univ Chicago Press, 2017)
Premise of research. Orectanthe consists of only two species with a distribution limited to the Guayana Highlands, in locations where sample collection is challenging. The genus belongs to Abolbodoideae, one of the two subfamilies of Xyridaceae. The development of the ovule, fruit, and seed of Orectanthe sceptrum was studied using a comparative approach to provide useful information for the taxonomy and phylogeny of the family. Methodology. Flowers and fruits at different developmental stages were analyzed by light and scanning electron microscopy. Optimization of select characters on a previously published phylogeny was conducted to evaluate the evolution of some embryological characters in Poales. The seed weights of O. sceptrum and species of Abolboda and Xyris were measured for comparison. Pivotal results. Orectanthe sceptrum presents anatropous, tenuinucellate, and bitegmic ovules with a micropyle bounded by both integuments. The multilayered outer integument forms the seed wing, which is a unique feature of this genus. The development of megagametophyte is of the Polygonum type. The seed has a tanniferous hypostase, a starchy endosperm, and a reduced and undifferentiated embryo. The seed coat is composed of a tanniferous tegmen (endotegmen and exotegmen) and testa (endotesta and exotesta). The mechanical layer of the seed coat is the exotesta. The fruit has a sclerenchymatous exocarp. The ancestral character-state reconstructions show that anatropous, crassinucellate ovules, megagametophyte development of the Polygonum type, and nuclear endosperm are the ancestral conditions in Poales. Orthotropous, tenuinucellate ovules appear in the most recent common ancestor of the xyrid, restiid, and graminid clades. The seed weight of O. sceptrum is one to two orders of magnitude greater than the seed weight of Abolboda and Xyris species. Conclusions. Anatropous ovules and a seed coat formed by endotegmen, exotegmen, endotesta, and exotesta link Orectanthe to Abolboda (Abolbodoideae). Such characteristics are not found in Xyris (Xyridoideae), which is consistent with the subfamilial division. The presence of anatropous ovules in Abolbodoideae most likely represents a character reversal. The greater seed weight of O. sceptrum may explain the presence of wings in the seeds.
Keywords: Abolbodoideae; character evolution; megasporogenesis; megagametogenesis; xyrids; winged seeds